Obstetric violence: perspectives from mothers, midwives, and obstetricians - Reyes-Amargant, Zaira; Fuentes-Pumarola, Concepció; Roqueta-Vall-llosera, Marta; Garre-Olmo, Josep; Ballester-Ferrando, David; Rascón-Hernán, Carolina (Frontiers in Global Women's Health, 2025)
BackgroundAccording to the World Health Organization (WHO), the majority of the 140 million annual births occur without complications. Women desire a positive birth experience based on respectful care, clear information, and emotional support, which enables them to make informed decisions and maintain control over their reproductive process. However, many women experience disrespectful or abusive treatment during obstetric care, with lasting consequences for both their physical and mental health. This study explores the factors that influence respectful maternal care and the phenomenon of obstetric violence, as perceived by mothers, midwives, and obstetricians.MethodologyA qualitative study using a phenomenological approach was conducted in eight public and private hospitals in the Girona Health Region (Catalonia, Spain) between 2021 and 2022. In-depth interviews were conducted with eight mothers and eight healthcare professionals (midwives and obstetricians) selected through purposive sampling. The interviews were transcribed verbatim and analysed using thematic analysis to identify meaningful units and key themes.ResultsThe narratives collected allowed for the identification of key elements of non-respectful maternal care. A lack of information during pregnancy and childbirth emerged as a central concern for both mothers and professionals, affecting their sense of control and satisfaction. Poor communication with healthcare providers, particularly with anaesthesiologists and obstetricians, was perceived as a barrier to quality care. Mothers reported experiences of disrespect, the absence of informed consent for procedures such as episiotomies, and paternalistic treatment. Obstetricians showed resistance to the term “obstetric violence,” while midwives recognized it as practices and attitudes that negatively affect the maternal experience.ConclusionsThe discrepancy between professional perspectives and mothers' experiences highlights the urgent need for transformation in obstetric care. It is crucial to promote a care model based on evidence, effective communication, and respect for women's rights. Incorporating a gender perspective into healthcare training and strengthening public policies to ensure respectful obstetric care are essential measures to improve the quality of care and prevent obstetric violence.